Metastasis of a Prostatic Carcinoma along an Omental Graft in a Dog - Terry M. Jacobs; Bruce R. Hoppe; Cathy E. Poehlmann; Marie E. Pinkerton; Milan Milovancev (Case Reports in Veterinary Medicine)
An 11-year-old male American Bulldog was presented for hematuria and tenesmus. It had been treated for chronic bacterial prostatitis with abscessation two years earlier and underwent castration and a prostatic omentalization procedure. There was no histologic evidence of prostatic neoplasia at that time. On physical examination, an enlarged prostate was found by rectal palpation, and it was characterized with ultrasonography and computed tomography. Surgical biopsies were obtained, and histopathology identified prostatic adenocarcinoma. It received carprofen and mitoxantrone chemotherapy in addition to palliative radiation therapy; it was euthanized six weeks later due to a progression of clinical signs. Necropsy findings included marked localized expansion of the prostatic tumor and dissemination of prostatic carcinoma cells throughout the peritoneal cavity along the omental graft with infiltration onto the serosal surfaces of most abdominal viscera and fat. This case represents a previously unreported potential complication of the omentalization procedure wherein carcinoma cells from a prostatic tumor that independently arose after omentalization may have metastasized along the surgically created omental graft.